The impact of working capital management on corporate performance: A study of firms in cement, chemical and engineering sectors of Pakistan - Mohammad Shaukat Malik; Mahum Bukhari (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The objective of this study is to investigate the impact of working capital management (WCM) on corporate performance in cement, chemical and engineering sectors of Pakistan. Data is obtained from annual reports of the companies during 2007-2011. Pooled ordinary least squares method is used to estimate the relationship between the measures of working capital management and performance. WCM measures include average age of inventory, average collection period, average payment period, operating cycle, and the cash conversion cycle whereas return on equity is used as a measure of firm performance. Leverage and firm size are taken as control variables. Results indicate that average payment period negatively and significantly whereas cash conversion cycle positively and significantly relate with return on equity. While, average collection period and operating cycle positively and insignificantly whereas average age of inventory negatively and insignificantly relates to the return on equity. In short WCM influences the corporation's performance.
Keywords: 330; average collection period; average age of inventory; average payment period; operating cycle; cash conversion cycle; return on equity